Pariwisata Dan Kerentanan Konflik: Kasus Pada Daya Tarik Wisata Pantai Kaluku Kabupaten Donggala - Amir, Andi Mascunra; Zaiful, Zaiful (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i01.p08, 2021)
The tourism sector fosters social change, including the emergence of friction of interests that leads to land / space conflicts. This research aims to explain: (1) Kaluku Beach tourism object as a realm of struggle for economic capital; (2) failure of economic capital management and lack of village leadership authority impacted massively barrier in tourism sector. Research results show that Kaluku beach tourism area is a field of conflict interest in terms of economic capital, leads to worst impact on tourism object management, low rates visiting. The absence of spatial planning and lack of village leadership authority caused conflict vulnerability, requires symbolic capital influence from village leader as dispute resolution. Suggestion for village leaders that they take consideration spatial planning in urgent, utilization of local resources and push social readiness towards social changes. Key words: Kaluku beach tourism, Land dispute, symbolic capital